The Influence of Copyright or Patent Rights on Sihobuk Peanut Products (Study on Tarutung Sihobuk Peanut Business) - Sabda Dian Nurani Siahaan; Dziban Ali Ashab; Putriayu Sryanta; Zilla Angeliani; Rachel Napitupulu (Formosa Journal of Science and Technology, 2023)
Sihobuk peanuts are nuts originating from Sihobuk Village, Tarutung, North Tapanuli. Sihobuk is a brand name taken from the name of a bean producing village. Not different from other nuts, Peanut Sihobuk has a savory and crunchy taste. Peanut Sihobuk is a kind of snack / snack that can make the audience not want to stop eating it. It is believed that the Sihobuk peanut market will grow rapidly in the future. This was triggered by the designation of Lake Toba as a major tourist destination and the inauguration of Silangit airport as an international airport. Many tourists will visit the North Tapanuli area and will definitely look for local culinary delights, including Sihobuk beans. Copyright or Patent is a right to protect a product or a work. Where protected products are guaranteed by state law. This allows the product to not be imitated or plagiarized by other competitors who are competing in selling other regional specialties.